Governance, sovereignty and profane hope in a globalised catastrophe-world - Naishtat, Francisco (2010)
This is a paper in political philosophy. It starts by an analysis of Walter Benjamin's notion of "baroque sovereignty'' as an implicit transformation of Schimitt's categories of sovereignty, decision and state of exception. It then discusses whether the dynamic between these concepts, as emanating from Benjamin's work, is fit to make diagnosis of our own current condition, marked by fragilised sovereignties, by global-intensive governance apparatuses and by a horizon-less catastrophe- world in which, paradoxically, the vision of the world diminishes in proportion as its technological visibility becomes ever greater through the simultaneous and instantaneous availability of images. To this effect, it discusses different theses in contemporary political reflection, and takes these concepts onto a concrete political and social situation, i.e. contemporary Argentina.